Disaster Mitigation: Optimizing the Function of Executive and Legislative Institutions in Handling Covid-19 - Anifatul Kiftiyah (International Journal of Social Science and Religion (IJSSR), 2020)
Through Presidential Decree (Keppres) Number 12 of 2020 the President has designated Covid-19 as a National Disaster. Handling Covid-19 requires good cooperation between elements, both society, government and state institutions. The President as an executive institution and the DPR as a legislative institution have very broad functions and powers in dealing with the Covid-19 pandemic. Namely, by optimizing the functions and powers it has in dealing with Covid-19 by establishing policies that aim to overcome Covid-19 without bringing political interests. This study uses a phenomenological research method with a normative juridical approach. With a descriptive analysis thinking method that aims to explain what is happening in the community and the government's anticipation in dealing with the Covid-19 pandemic. The results of this study are that the executive and legislative bodies must be more maximized and more assertive in implementing policies to deal with covid-19.